G588(P) Scrub typhus: a series of cases in a tertiary care centre from april 2018 to july 2019. (25th October 2020) - Sahariah Khound, G; Khaund Borkotoky, R; Saha, AL; Banerjee Barua, P; Das, B; Khound, N; Pathak, S
Abstract : Aim: Although Scrub Typhus is an endemic disease, it is grossly underdiagnosed owing to the nonspecific clinical presentation, lack of access to specific diagnostic facilities in most areas and low index of suspicion by the clinician. Our aim of the study is to increase the awareness of the disease amongst the clinicians. Methods: Seven patients with acute febrile illness diagnosed to have scrub typhus are reported here with varied presentations from April 2018 to July 2019. First case presented with fever, headache, cough with shortness of breath in the month of April 2018. Second case presented with fever with chills and rigors, cough, respiratory difficulty, passage of dark coloured urine in May 2018. Third case presented with fever, breathing difficulty, multiple eschars, two episodes of cardiac arrest and vomiting in Sept 2018. Fourth case presented with fever, pain abdomen, breathing difficulty, passage of black coloured stool in May 2019. Fifth case presented with fever with chills and rigors, cough, erythematous rashes over face, hands, legs and body and an eschar on left axillae in May 2019. Sixth case a six month old infant with fever and rashes all over the body, eschar on left leg and passage of loose stool in the month of June 2019. Seventh case presented with fever with breathing difficulty, yellowish discoloration of urine, generalized oedema, in the month of July 2019. To diagnose the cases we used immunochromatographic ( IgM and IgG ) study for scrub typhus. Due to resource constraints we couldn't use Immunofluorescence Antibody ( IFA ) to confirm the diagnosis. Doxycycline with other supportive medications rapidly altered the clinical course without any sequelae. Results: All the patients responded well to Doxycycline and other supportives. Defervescence occurred in 24 to 48 hours of using first dose of Doxycycline. Conclusion: High index of suspicion, timely diagnosis and appropriate treatment can reduce the morbidity and mortality of Scrub Typhus.